MODERN SYSTEMS OF PERSONNEL SELECTION AS A BASIS FOR THE HUMAN CAPITAL FORMING AT THE ENTERPRISE (Regional aspects of productive forces development of Ukraine, 2019)
The article examines the essence, main advantages and disadvantages, as well as the tools of selection and selection of personnel at modern enterprises. In particular, external sources (consulting, outsourcing, Internet, recruiting, the State Employment Service) and internal (Internet, universities, media, own resumes, personal contacts, fairs) of the source are classified as the main methods of employee search.The main methods for recruiting staff were interviewing, Brainteaser-interviews, stressinterviews, physiognomy and others. The efficiency of using the methods of selection and selection of personnel in modern economic conditions for increasing the profitability of business entities has been proved.